ANALISIS NILAI TUKAR USAHA PEMBUDIDAYA IKAN DI KABUPATEN BANDUNG - Aulya, Anggrila; Suryana, Asep Agus Handaka; Apriliani, Izza Mahdiana; Nurhayati, Atikah (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2025)
Bandung Regency is famous as a fisheries center in West Java Province. Freshwater fish farming is one of the main economic activities for many residents in this region. One of the indicators that can be used is the Fish Farmers Business Exchange Rate (NTUP), to asses the wlfare of fish farmers. This research aims to analyze the exchange rate of fish cultivating businesses (NTUP) and the NTUP of Bandung Regency. The research method used is a survey with interview techniques using a questionnaire. Primary data were collected by observation and interviews with a total of 90 respondents (42 tilapia farmers, 13 goldfish farmers, 35 catfish farmers). Secondary data is obtained from the relevant Installation Office and other data sources. The data analysis used is quantitative descriptive. Based on the research results, it can be concluded that most of fish farmers in Bandung Regency have NTUP > 100, which shows that fish farmers in Bandung Regency are at a prosperous level. The results of multiple linear regression shows that age, education level, work experience, expenditure and income influence the NTUP of Bandusng Regency. based on the F test, the independent variables simultaneously influence NTUP, while partially the factors that influence significantly are income and expenditure. Variables that do not significantly influenced are: land area, age, education level and work experience